Language Teaching Training with QnA Method for Early Childhood at TKQ Nur'aeni Cibatu - Lina Siti Nurwahidah; Umi Kulsum; Ari Kartini; Agus Haris; Nuralyani Nuralyani (Fakultas Kewirausahaan Universitas Garut, 2021)
Abstract Indonesian language skills are basically formed due to training both naturally and through education. Language skills are needed as a means of community life skills. Likewise, at an early age, children who are in this golden age need to be well supported by their skills. At TKQ Nura'eni, Indonesian language teaching training is carried out so that students can learn. Teachers realize that students' linguistic potential must be directed and supported. The linguistic potential of students has been directed to three languages, namely regional languages, Indonesian and Arabic. This is because the students had previously been in contact with Arabic in their daily routines, namely through reading Iqra, the Koran, and memorizing prayers. This linguistic potential must be developed. So this counseling is carried out using a method that has been adapted to the cognitive development stage of early childhood, namely the QnA teaching method through singing activities. This will make it easier for children to process the language material that is being delivered. It turned out that the results were very maximal, and supported their language development in getting to know them in various ways. Abstrak Keterampilan berbahasa Indonesia pada dasarnya terbentuk karena adanya latihan baik secara alami maupun melalui pendidikan. Keterampilan berbahasa diperlukan sebagai alat kecakapan hidup masyarakat. Bagitu pula pada usia dini, anak-anak yang berada pada masa emas ini perlu untuk didukung keterampilanya dengan baik. Di TKQ Nura’eni ini dilakukan pelatihan pengajaran bahasa Indonesia agar dapat dipelajari siswa. Para pengajar menyadari bahwa potensi kebahasaan siswa harus diarahkan dan didukung. Potensi kebahasaan siswa sudah diarahkan pada tiga bahasa yaitu bahasa daerah, bahasa Indonesia dan bahasa Arab. Hal ini dikarenakan para siswa sebelumnya sudah bersentuhan dengan bahasa Arab dalam rutinitas kesehariannya, yaitu melalui kegiatan membaca Iqra, Alquran, serta hafalan doa-doa. Potensi kebahasaan ini tentu harus dikembangkan. Maka penyuluhan ini dilakukan dengan metode yang telah disesuaikan dengan tahap perkembangan kognitif anak usia dini, yaitu metode pengajaran QnA melalui kegiatan bernyanyi. Hal ini akan mempermudah anak untuk memproses materi bahasa yang sedang disampaikan. Ternyata hasilnya sangat maksimal, dan mendukung perkembangan bahasa mereka dalam mengenal mereka pada berbagai hal.